Team of rivals: Co-opetition for technology start-ups - Shah, Snehal (Institutional Knowledge at Singapore Management University, 2017)
A business environment characterised by cloud computing, driverless cars and artificial intelligence has prompted a fundamental shift in the way we think of existing business models. Market sizes have transcended geographic boundaries and New Age firms typically target much larger populations than new firms did a decade ago. Today, meaningful value is derived when a company is an active participant in shaping the environment to one’s own strategic advantage.